The drinking water crises of Flint and Havelock North: a failure of public health risk management - S. J. McLaren; M. W. Sahli; S. Selig; S. J. Masten; W. H. Page (IWA Publishing, 2022)
Between 2014 and 2016, there were two severe community water system (CWS) failures in Flint, Michigan (MI), USA and Havelock North, Hawkes Bay, New Zealand. These events had profound implications for public health in their respective countries. While the nature of both crises was different, certain aspects of the failings were strikingly similar. These included: failure of authorities to protect the integrity of their source water,; 'wait-and-see approach' to address problems if and when they occurred,; negligent approach to regulatory oversight and responsibility,; substandard facilities and lack of knowledge and training of staff,; failure of consultants and advisory services engaged by suppliers, and; failure of government agencies to enforce regulations.; The lessons from both incidents must be learned, or similar tragic events are likely to reoccur. The six principles identified in the Government Inquiry into the Havelock North outbreak are an essential first step. The next step is to implement them throughout the drinking water sector. HIGHLIGHTS The drinking water crises in Flint, MI and Havelock North, NZ are compared.; The failings in these crises were found to be strikingly similar.; The crises in both locations involved a disregard for public health.; The six principles laid out in the Government Inquiry into Havelock North incident can be broadly applied worldwide to protect human health.;